The watchers - Shine, A. M. (Head of Zeus, 2022)
This forest isn't charted on any map. Every car breaks down at its treeline. Mina's is no different. Left stranded, she is forced into the dark woodland only to find a woman shouting, urging Mina to run to a concrete bunker. As the door slams behind her, the building is besieged by screams. Mina finds herself in a room with a wall of glass, and an electric light that activates at nightfall, when the Watchers come above ground. These creatures emerge to observe their captive humans and terrible things happen to anyone who doesn't reach the bunker in time. Afraid and trapped among strangers, Mina is desperate for answers. Who are the Watchers and why are these creatures keeping them imprisoned, keen to watch their every move?